HOW DOES THE ROLE OF POLITICAL CONNECTIONS INFLUENCE THE CORPORATE SOCIAL RESPONSIBILITY SCORES - Arief Nurhandiaka (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study —The objective of this study is to examine the impact of the board of commissioners and directors on CSR scores. Research method—This research adopts a quantitative approach and employs purposive sampling to select samples. The sample comprises 17 companies in the IDX-IC sector A for the period spanning from 2016 to 2021. Panel data regression analysis is utilized for the empirical analysis, with STATA software being employed for the statistical computations. Result— The findings reveal that having a politically affiliated board of commissioners, the variable concerning politically affiliated board, and the variable concerning politically affiliated audit committee positively influences CSR scores. Conclusion— The implications of this study shed light on how companies or practitioners address political affiliations while considering CSR values, particularly in light of social conditions such as the Covid-19 pandemic, elections, and other matters that involve new government regulations pertaining to social responsibility.